(untitled) (Physical Education, Health and Social Sciences, 2025)
Pharmaceuticals are major sectors in terms of economic growth and public health, but the pharmaceutical exports from Pakistan are happening on account of various challenges. Some of the prime barriers are delays in regulatory approvals, high registration costs, trade barriers, supply chain inefficiencies, and a lesser local availability of Active Pharmaceutical Ingredients (API). Moreover, a few local bioequivalence testing facilities and their high costs of international certifications also restrict the global competitiveness of Pakistani pharmaceutical exports. The quantitative research method supporting deductive methodology has been applied in this study. A cross-sectional design comprises collecting data from professionals in the pharmaceutical export sector using self-administered questionnaires. Findings indicating the presence of regulatory inefficiency, financial constraints, and infrastructure inadequacy are holding a very significant impact on the export performance of local manufacturers making it difficult to compete globally. The adoption of international certifications and the establishment of bioequivalence testing facilities with export incentives would also pay much contribution to the establishment of a Pharmaceutical Special Economic Zone (SEZ). All of these have to be in place so that these barriers are lifted from struggling pharmaceutical exporters, giving them latitude to work with less operational hurdles and more compliance with global standards in opening up new market opportunities. This research provides appreciation for stakeholders and policymakers, showing how to strengthen Pakistan against the global pharmaceutical market.